(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the events of Russian-Turkish war 1735-1739. The questions of war company of 1736-1737 you find in archives of V. Vernadsky National Library of Ukraine. New researches of archival funds of V. Vernadsky National Library to refute historical myths of Russian-Turkish war 1735-1739. Key words: Cossack, fortress, Russian-Turkish war.